Integrating Geographic Information into the Analysis of the Genetic Distribution of South African Vervet Monkeys - (:unkn) unknown (My University, 2020)
This project uses the program Geneland to reanalyze McAuliffe’s (2008) thesis data on genetic variability in three South African vervet monkey populations (Polokwane, Oribi and Blyde). Using information on the geographic location and genetic variability of these populations, the spatially explicit Geneland program shows that the three populations are weakly differentiated. These findings oppose the results of previous genetic studies of South African vervet monkeys as well as the results obtained by McAuliffe with the spatially implicit Structure program, which found that the 34 individuals all come from one population. Based on this historic data and the fact that other studies have found the same number of subpopulations with both Structure and Geneland, I conclude that Polokwane, Oribi and Blyde are slightly differentiated, though not distinct enough to be considered separate populations (Latch et al. 2008). These results need to be supported by an analysis of the entire sample of South African vervet monkey genetic data from up to 200 animals prior to suggesting policy changes regarding genetic structuring in South African vervet monkeys.